O papel do sindicalismo da agricultura familiar no acesso às políticas públicas de desenvolvimento rural - Simonetti, André Luiz (2023)
The Brazilian family farming unionism develops as agriculture begins to take shape and become economically important in the country. However, such unionism was only regulated in 1963, in an attempt by the State to control the incipient movements of rural workers and small landowners. In the West of Santa Catarina, it emerged in the mid-1960s, influenced by the actions of the Catholic Church, and family farming unionism, at the time concentrated in the Rural Workers' Union, emerged in São Lourenço do Oeste in the 1970s, and was consolidated as the main entity defending family farming in the municipality to this day. Such unionism is an important tool in the struggle for farmers to gain rights and a space to claim against the State. Therefore, the objective of this work is to understand the role of the Union of Workers in Family Agriculture of São Lourenço do Oeste and Novo Horizonte, through a historical review, with its basis in the organization of family farmers and the articulation of social actors in the promotion of public policies and actions for local rural development, motivated by the following research question: how did SINTRAF in São Lourenço do Oeste and Novo Horizonte contribute to the organization of family farmers and the articulation of various social actors in promoting local rural development? To this end, a sociogenesis of SINTRAF was carried out, starting from an exploratory research on the entity's fifty years, identifying its main articulators, which are four former presidents, a state agent and a farmer associated with the entity since 1971. In a second stage , these organizers and fourteen families from the union base were interviewed. In the interviews with the families, their production systems and the use of public policies constructed or accessed through union struggle were analyzed. All interviews were analyzed using the content analysis method. In a third stage, all minutes of management meetings and general assemblies were read, in addition to other pertinent documents, to complement the collection of information from the interviews. It is noteworthy that the union's actions, in the construction of public policies, in fact promote quality of life for farmers. When analyzing chronologically, these struggles sought health care and social security, later advancing to access to agricultural credit, improving farmers' working and production conditions. Subsequently, action on quality of life, with housing policy, increasing income with market access policies (such as PAA and PNAE). In addition to these macro issues, other specific issues had space in the entity, such as land credit, the struggle to resolve seasonal and local problems, in addition to municipal claims that were raised by the base or perceived by the directors.